KONSENTRASI TIMBAL (Pb) PADA PERAIRAN DI SEKITAR TELUK JAKARTA - Maman Rumanta; Amril Latief; Ucu Rahayu; Anna Ratnaningsih; Gusti Nurdin (Jurnal Matematika Sains dan Teknologi, 2008)
he purpose of this study is to get information about river that has the greatest contribution to cause Pb pollution in the Jakarta Bay. Nine (9) of 13 rivers flowing into Jakarta Bay were chosen. They were Citarum, Bekasi, Cilincing, Marunda, Ciliwung, Sunter, Cideng, Angke, and Cisadane. Sampling were taken in two periods of times, rainy and dry season of 2006 with triple repeatations. pH and temperature of samples as proponent data were measured insitu. Pb concentration in the water of the river was measured by using AAS flame in the laboratory of Balai Penelitian Tanah Bogor. Data was analyzed statistically (one way ANOVA and t-test) by using SPSS 11.5 software. It was shown that Pb concentration of estuary water surrounding Jakarta Bay has been exceeding threshold level. There was a tendency that Pb concentrations of water in rainy season are lower than that in dry season except in Ciliwung River. The anomaly of Ciliwung River was probably caused by some industries which throw their wastes into Ciliwung River in the rainy season. It was concluded that all of 9 rivers have a significant contribution to Pb pollution in Jakarta Bay, and the most was from Ciliwung River.